2019
DOI: 10.1017/s0144686x19000072
|View full text |Cite
|
Sign up to set email alerts
|

‘Just another day’: the lived experience of being a hundred years old for ten New Zealanders

Abstract: The aim of this study was to gain an understanding of the experiences of extended longevity as perceived by centenarians. Centenarians (people over 100 years of age) are the fastest growing group of the ageing population in developed countries. Ten centenarians aged between 100 and 106 years, living in the Lower North Island of New Zealand, participated in the study. The biographical narrative interpretive method of inquiry guided data collection through face-to-face interviews, and thematic analysis was subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…However, for our centenarians, it was having the desire to live a good life that allowed them to see the beauty of living, to appreciate the simpler aspect of life and to find their purpose, reason for being. These sub-themes are supported by research where centenarians shared that a focus on living a good life significantly contributed to their longevity (Zeng and Shen, 2010; Hutnik et al , 2016; Scelzo et al , 2018; Ratan and de Vries, 2020). Furthermore, centenarians believe that they deal with and positively process very difficult life events because they consider themselves ‘lucky’ or ‘fortunate’ (Hutnik et al , 2016), embrace ‘laughter as an important part of their life’ or adopt an optimistic and communicative lifestyle (Kato et al , 2012).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, for our centenarians, it was having the desire to live a good life that allowed them to see the beauty of living, to appreciate the simpler aspect of life and to find their purpose, reason for being. These sub-themes are supported by research where centenarians shared that a focus on living a good life significantly contributed to their longevity (Zeng and Shen, 2010; Hutnik et al , 2016; Scelzo et al , 2018; Ratan and de Vries, 2020). Furthermore, centenarians believe that they deal with and positively process very difficult life events because they consider themselves ‘lucky’ or ‘fortunate’ (Hutnik et al , 2016), embrace ‘laughter as an important part of their life’ or adopt an optimistic and communicative lifestyle (Kato et al , 2012).…”
Section: Discussionmentioning
confidence: 88%
“…They give context to the positive association between adaptation and family involvement when describing centenarians’ adaptability to adverse changes (Hensley et al , 2010; Scelzo et al , 2018; Ratan and de Vries, 2020). Through these sub-themes, it is evident that inner resources contribute to an association between thriving and socialisation in the community (Dubovská et al , 2017; Levasseur et al , 2017; Kok et al , 2018; Ratan and de Vries, 2020). Furthermore, the research supports how these sub-themes reflect thriving even when living in poverty and/or economically distressed conditions from unavoidable situations (Bennett et al , 2016; Kok et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, other studies have endeavored to identify specific factors related to extreme longevity (Andersen-Ranberg et al, 2001; Christensen & Vaupel, 1996; Herr et al, 2018; Maier et al, 2020; Motta et al, 2005). Most of these previous studies have employed quantitative designs, focusing on biological and physiological aspects and family background; meanwhile, a small number of studies have used qualitative designs to analyze psychosocial and psychoemotional aspects or centenarians’ personal biographies (Darviri et al, 2009; Hutnik et al, 2012; Reichstadt et al, 2010; Poon & Cheung, 2012; Poon et al, 2007; Ratan & de Vries, 2020; Struckmeyer et al, 2020; Wong et al, 2014); such approaches can clarify centenarians’ own understanding of their longevity and the aspects they themselves feel have enabled them to maintain their cognitive faculties. The studies that have adopted the latter approaches have identified several factors, including maintaining a positive outlook on life, keeping mentally and physically fit at all times, nurturing family and social relations (Wong et al, 2014), obtaining wellness and happiness and having an extroverted character (Jopp & Rott, 2006; Struckmeyer et al, 2020), and being resilient and controlling sources of frustration (Hutnik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%